2018
DOI: 10.3892/etm.2018.6143
|View full text |Cite
|
Sign up to set email alerts
|

A cynomolgus monkey model of carotid atherosclerosis induced by puncturing and scratching of the carotid artery combined with a high‑fat diet

Abstract: Cardio-cerebrovascular disease is one of the three major causes of mortality in humans and constitutes a major socioeconomic burden. Carotid atherosclerosis (CAS) is a very common lesion of the arterial walls, which leads to narrowing of the arteries, in some cases occluding them entirely, increasing the risk of cardiovascular events. The aim of the present study was to evaluate a cynomolgus monkey model of carotid atherosclerosis (CAS) induced by puncturing and scratching combined with a high-fat diet. A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Endothelial cell damage is the initiating pathological basis of arteriosclerosis, and runs through the whole process of arteriosclerosis development. The dysfunction of vascular endothelial cells and activation of the inflammatory response ultimately cause the occurrence of CAS [ 3 ]. In the current study, HAECs were recruited for cell function experiments and treated with oxLDL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endothelial cell damage is the initiating pathological basis of arteriosclerosis, and runs through the whole process of arteriosclerosis development. The dysfunction of vascular endothelial cells and activation of the inflammatory response ultimately cause the occurrence of CAS [ 3 ]. In the current study, HAECs were recruited for cell function experiments and treated with oxLDL.…”
Section: Discussionmentioning
confidence: 99%
“…The main cause of CAS is the dysfunction of endothelial cells caused by atherosclerotic plaque, and the apoptosis of vascular endothelial cells induced by oxidized low-density lipoprotein (ox-LDL) is a vital link leading to the lesion [ 2 ]. It is demonstrated that age, hypertension, diabetes, and hyperlipidemia are all risk inducements for CAS [ 3 ]. Clinical intervention for asymptomatic CAS patients can effectively reduce the risk of stroke, which has an important clinical significance.…”
Section: Introductionmentioning
confidence: 99%
“…4 The main pathological changes include vascular endothelial cell damage, inflammatory cell infiltration, abnormal lipid deposition, foam cell formation, and atherosclerotic plaque formation. 5 The risk factors of CAS factors include obesity, hypertension, hyperlipidemia, smoking, chronic infection, and genetic factors. Many patients with CAS often have no obvious clinical symptoms, while acute ischemic symptoms, such as sudden stroke and hemiplegia, are often caused by carotid plaques or thrombus on the surface of plaque, leading to intracranial arteriovenous ischemia.…”
Section: Introductionmentioning
confidence: 99%